Um modelo de otimização para as operações de produção de vapor em caldeiras industriais: um estudo de caso na indústria de alimentos - Rocco, Cleber Damião (2011)
The aim of this work was to develop and apply a mathematical optimization model to support some key decisions in the steam production operation system with multiple industrial boilers. In the food industry, key decisions into this system are, normally, taken based on people experience, not through decision support tools based on operations research. The proposed model approaches the fuel replenishment decisions, fuel transportation and fuel inventory management. The model also determines the start-up and shutdown moments for each boiler, as well as, which of them will produce steam. An algebraic modeling language was used to implement computationally the model, which was solved by an optimization software. The adjustments and model validation were performed through a case study carried out in a large scale food industry localized in Goiania (GO). In computational experiments conducted with company s data, the results obtained by the model showed better economic performance than those from the company. In face of the good outcomes obtained by applying the model and the lack of protocols or decision tools for the studied system, this model presents itself as a feasible alternative to be considered to support some key-decisions in the steam production system with industrial boilers.